What worries farmers? An analysis of the queries raised at Kisan Call Centres - S, Yashvanth B; K, Soam S; Ch, Srinivasarao (Indian Farming, 2021)
This study uses the text data fromthe queries raised at KCC from thefarmers of Nizamabad district ofTelangana during the agriculturalyear 2016-17 to identify theproblems often encountered by them.There were 1,384 queries raised bythe farmers of which most of thequeries were on weather and plantprotection (72.8% together). Fromthe word cloud drawn, it is observedthat a noticeable number of queriesare related to weather underlining theimportance of timely communicationof weather information to thefarmers. The results highlight theneed for popularizing other ICTinterventions like push messages andweather apps to send timely weatherrelated information to farmers.